Pengembangan Lembar Kerja Siswa (LKS) Bernuansa Quantum Teaching Untuk Meningkatkan Minat Dan Hasil Belajar Siswa Kelas IV Di Sekolah Dasar - Desi Widiyanti; Khairil Hadi (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: The purpose of this study was to determine the results of the development of LKS nuanced quantum teaching and increased student interest and learning outcomes. This research uses educational development method with 4D Models Thiagarajan, but only consists of 3 (three) stages, namely the defining stage, the planning stage, and the developing and disseminating stages. The population and sample are grade IV students. Data collection instruments used consisted of LKS validation sheets, teacher and student response questionnaires, student interest questionnaires, student interest observation sheets, pretest and posttest. Data analysis uses a Likert scale by changing quantitative values ​​into qualitative values. The results of this study note that the results of the product development in the field of quantum teaching have a very good category so that it is feasible to be used as teaching material in science lessons. Students are very interested in the product development of LKS nuanced quantum teaching as the results of the average percentage of students' interest in LKS is 85.42%. The results of LKS development products have been able to improve student learning outcomes as the results of the average percentage of pretest practice questions by 51.94% and in posttest practice questions by 73.78%. Abstrak: Tujuan penelitian ini adalah untuk mengetahui hasil pengembangan LKS bernuansa quantum teaching dan peningkatan minat dan hasil belajar siswa. Penelitian ini menggunakan metode pengembangan pendidikan dengan 4D Models Thiagarajan, tapi hanya terdiri dari 3 (tiga) tahap yaitu tahap pendefinisian (define), tahap perencanaan (design), dan tahap pengembangan (develop) dan penyebaran (disseminate). Populasi dan sampel adalah siswa kelas IV. Instrumen pengumpulan data yang digunakan terdiri dari lembar validasi LKS, angket respon guru dan siswa, angket minat siswa, lembar observasi minat siswa, pretes dan postes. Analisis data menggunakan skala likert dengan mengubah nilai kuantitatif menjadi nilai kualitatif. Hasil penelitian ini diketahui bahwa hasil produk pengembangan LKS bernuansa quantum teaching memiliki kategori sangat baik sehingga layak untuk digunakan sebagai bahan ajar pada pelajaran IPA. Siswa sangat berminat terhadap produk pengembangan LKS bernuansa quantum teaching sebagaimana hasil persentase rata-rata minat siswa terhadap LKS yaitu 85,42 %. Hasil produk pengembangan LKS telah dapat meningkatkan hasil belajar siswa sebagaimana hasil persentase rata-rata soal latihan pretest sebesar 51,94 % dan pada soal latihan postest sebesar 73,78 %.